ANÁLISIS DE LA INFRAESTRUCTURA DE LA RED ETHERNET DE LA CORTE PROVINCIAL DE JUSTICIA DE LA CIUDAD BABAHOYO. - Olvera Pino, Stalyn Wilfrido (2018)
One of the main concerns of the systems department of the Provincial Court of Los Ríos, now known and annexed to the (Council of the Judiciary), is the distribution of information through its computer network in relation to the handling of their information, between these: computer equipment, services, data, human resources and auxiliary equipment. Through analysis and observation based on infrastructure and different sources on network security due to lack of updating and maintenance of the same; a case analysis was carried out to verify if it is adequate or could cause failures in the infrastructure of the computer network of the provincial justice court of the city of Babahoyo, if the devices or components are constantly updated (tangible and intangible) , the advance in information network programs, the computer network management system and the legal interests against the provincial court of justice, will bring with it the possibility of the action of external or internal agents to the systems department of the company. One way to reduce shortcomings that arise in the Babahoyo Provincial Court of Justice is to modernize its network devices with modern ones that implement security and adequate standards for the protection of information and communication security, due to the fact that through research it was possible to Note that some devices are obsolete at their normal lifespan.